PIDOTIMOD IN PAUCISYMPTOMATIC SARS-CoV2 INFECTED PATIENTS - Claudio Ucciferri; Barone Mirko; Jacopo Vecchiet; Katia Falasca (Mediterranean Journal of Hematology and Infectious Diseases)
Background and purpose: Currently clinicians wide world are facing with SARS-CoV-2 pandemy, whose clinical features include fever, dry cough, fatigue and acute respiratory distress syndrome (ARDS) which can progress to life threatening sequelae. Aim of this study is to evaluate both efficacy and safety of pidotimod in paucisymptomatic SARS-CoV-2 patients without any evidence of concurrent pneumonia.